Technology of Cognitive and its Effect on the Level of the Enzyme (Acetyl cholinesterase) and (Lactic Acid) and the Performance of most Important Offensive Skills in Fencing for Female Students - Hayder Naji Habash Alshawi (Journal of Global Pharma Technology, 2016)
The importance of research to the study of cognitive technology and its effect with the formulation of acetylcholinesterase and lactic acid for female students in the fencing, the problem of research was that the game of fencing of games of relatively small space requires the player to have positive qualities, so the researchers studied the effect of the enzyme acetylcholinesterase in technology of cognitive plus and lactic acid to achieve the best results, the objectives of the research were to identify the level of cognitive technology (Cogni Plus), acetylcholinesterase, lactate acid level, and the level of some physiological variables for female students in fencing, to identify the correlative relationship between the (Cogni Plus) level and the acetylcholinesterase and lactic acid in the fencing for female students, the researchers used the descriptive method in a survey and correlative method to suit the nature of the problem. The sample of the research included the players of the Middle and South Euphrates clubs in the youth fencing participating in the premier league for the 2016-2017 sports season, the nine clubs (Basra, Maysan, Muthanna, Wasit, Dhiqar, Rafidain, Solidarity, Babil and Karbala). The sample was selected in a simple random way, (20) players (10) for Al-Tadamon Sports Club and (10) for Al-Rafidain Sports Club. The researchers used the following tests: First: Cognitive Level of Cognitive Plus, Biochemical Variables, Lactic Acid concentration, and acetylcholinesterase concentration. The researchers concluded that cognitive cognition technology increased in players due to psychological effect they have. Decreased action of the enzyme acetylholinesterase due to the concentration of lactic acid in the muscle, which leads to slow work and send instructions, Increase the proportion of lactic acid in the muscles as a result of the high level cognitive technology (Cogni Plus) and recommended the adoption of the results of research and use by the trainers of the fencing to see the psychological effects of physiological fencing players. Attention to the psychological preparation of the players during the training process along with the physical, skill and plan numbers because of its importance in the reflection on the physical and physiological aspects of the performance. To establish a department of sports medicine in the faculties of physical education and sports sciences and provide all specialized devices in order to facilitate the task of carrying out research and studies. Conducting research and similar studies by researchers to standardize and define standard levels of cognitive technology scale (Cogni Plus) on individual and group games.Keywords: Cognitive technology, Acetyl cholinesterase, Lactic acid and fencing.